ABOUT CHARACTERS ON VILENKIN GROUPS - Pepić, Medo (Matematichki Bilten, 2008)
In this paper we proved that Lemma [7, p.727] is not true and that the following Theorem holds: Let \(G\) be Vilenkin group. Let \(k \in [m_n,m_{n+1})\) be natural number given by\[k=\sum_{j=0}^{n}k_jm_j,\qquad 1\leq k_n